2014
DOI: 10.1021/ja508059p
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast UV-Induced Photoisomerization of Intramolecularly H-Bonded Symmetric β-Diketones

Abstract: In photoinduced molecular reaction dynamics, the effects of electronic charge redistribution can lead to multiple pathways that are determined by the nature of the initial structures involved and the environment the molecule of interest is studied in. The β-diketones are a common example of this complexity. They show keto−enol tautomerism that is almost totally shifted toward the enolic form. However, compared to the gas phase, the photochemistry proceeds completely differently by virtue of the solvent environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
80
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 58 publications
8
80
3
2
Order By: Relevance
“…A detailed description of the utilized TA setup can be found elsewhere 27 . Briefly, a fraction of the fundamental beam from a commercial Ti:sapphire regenerative-amplifier laser system (Spitfire Pro, Spectra-Physics, center wavelength λ c  = 800 nm, pulse duration Δτ = 120 fs, repetition rate ν rep  = 1 kHz) was used to seed a commercial non-collinear optical parametric amplifier (TOPAS White, Light Conversion) which was frequency-doubled to generate the UV pump beam.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the utilized TA setup can be found elsewhere 27 . Briefly, a fraction of the fundamental beam from a commercial Ti:sapphire regenerative-amplifier laser system (Spitfire Pro, Spectra-Physics, center wavelength λ c  = 800 nm, pulse duration Δτ = 120 fs, repetition rate ν rep  = 1 kHz) was used to seed a commercial non-collinear optical parametric amplifier (TOPAS White, Light Conversion) which was frequency-doubled to generate the UV pump beam.…”
Section: Methodsmentioning
confidence: 99%
“…To directly observe ESIPT in the electronically excited state, time-resolved measurements with femto- to picosecond time resolution are required. The real-time dynamics of such a proton transfer in various ESIPT molecular systems have been explored in the gas phase, 6–10 techniques applied to ESIPT in solution comprise time-resolved fluorescence based on streak cameras, 11 time-correlated single-photon counting, 12–14 and upconversion, 12,15–17 as well as transient absorption (TA) with pump/probe combinations being UV/mid-IR, 2,16,18–20 UV/VIS, 12–14,16,19–29 and recently UV/UV 27,29 . Most of these ultrafast measurements have shown that ESIPT typically occurs on a subpicosecond time scale, with a key role for the low-frequency Raman-active modes modulating the H-bond distance between the proton donor and the acceptor atom 11,25,30–38 …”
Section: Introductionmentioning
confidence: 99%
“…b-diketones and their derivatives are of great importance in many fields by virtue of a number of interesting and specific properties originating from their dicarbonyl structures (UrbaniakDomagala, 2011;Verma et al, 2014). Acetylacetone (abbreviated as AA) is one of the simplest b-diketones.…”
Section: Introductionmentioning
confidence: 99%
“…With structural similarities to relevant biomolecules and photochromic substances, in combination with its structural simplicity, AA is a prototypical candidate for a systematic study of the photoinduced processes (Verma et al, 2014). The basic photophysical and photochemical processes of AA have been intensively investigated in gas phase (Zhou et al, 2008;Mayo and Takeshita, 1963;Yoon et al, 1999;Harrison and Lossing, 1959) and in isolated cryogenic matrices (Trivella et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Each cluster contains the four water molecules closest to the two oxygen atoms to explicitly include hydrogen bonding and first-solvation-shell-specific complexation; each cluster is surrounded by SMD continuum solvent. Figure 2 shows that the simulated ππ* absorption maximum of the CE conformer in water is slightly red-shifted to 262 nm (4.73 eV) with respect to that in the gas phase, in contrast to the distinct blue-shift observed 9 9 This raises the question: is the discrepancy due to inadequacies of the theory or have the experiments on this prototype molecule been misinterpreted? The conclusion of this letter will be that the latter answer is the correct one.…”
mentioning
confidence: 96%